Evolution of the fundamental individual rights to the spiritual sphere in the Civil and Commercial Code, and their perspective in the face of technological advance (Nueva Epoca, 2020)
Internet, social networks, artificial intelligence and other technological advances are reshaping the landscape of our social relationships. Their benefits are remarkable but at the same time they are the vehicles to novel attacks to the fundamental individual rights and their moral dimensions specially. Now it is common to injure the individual's honor and image through offensive and hate speech on the social networks, invasion of privacy through the use of artificialintelligence, cyber–espionage, and other similar techniques, and even the fraudulent change of our digital identities. The recognition of fundamental individual rights linked to our moralpersonality in the CCyCN has been an important milestone for the pro-tection of our dignity. Five years later of the enactment of CCyCN it's a good time to revisit its text and its purposes and exploring new legal dispositives such as the right to be forgot-ten, the right to be disconnect, theright to out digital image and the right to algorithm transparecy and its responsible use. Finally, I ask if our constitutional and civil rules about free speech are applicable to that new phenomena on balance or if, on the contrary, we need to develop a new set of legal principles.
Keywords: fundamental individual rights; free speech; internet; new injuries; proposed solutions